STUDY ABOUT ELECTROSTATIC AND ELECTRIC FIELD (International Journal of Engineering Sciences & Management Research, 2020)
An electric field (sometimes E-field), is a vector quantity that varies from point to point. All of us have the experience of seeking a spark or hearing a crackle when we take off our synthetic clothes or sweater particularly in dry weather. This is almost inevitable with ladies garments like polyester sari. The reason for these experiences is discharge of electric charges. Electrostatics deals with the study of forces, fields and potentials arising from static charges.